Authorship of some polychaete (Annelida) names derived from the works of Renier and Savigny - Muir, Alexander I.; Petersen, Mary E. (Zootaxa, 2013)
Full citations of animal specific or generic names ultimately derived from unpublished manuscripts should commemorate the work of the person who described the new species as well as the person who eventually validly published the name. We suggest that biologists should use the following authorships when citing these names: Terebella infundibulum Renier in Meneghini, 1847 (now used in the genus Myxicola); Nereis coccinea Renier in Meneghini, 1847 (now used in the genus Lumbrineris); Thalassema scutatum Renier in Ranzani, 1817 (now known as Sternaspis scutata); Polynoe Savigny in Lamarck, 1818. The case of Myxicola infundibulum is further complicated by a possible homonymy, and to avoid confusion we suggest that the name is used for the Myxicola species found in the Adriatic.